Lung involvement in accident victims: report of three cases - Chetambath, Ravindran; Parengal, Jabeed; Aslam, Mohammed; Shivashankaran, Sanjeev (International Journal of Research in Medical Sciences, 2017)
Lungs are target organ for damage during accidents and contribute significantly to the mortality of the victims. Here we present three different types of accidental injury to the lungs leading to respiratory failure and their varied presentations.